UPWELLING-DOWN WELLING DYNAMICS OF ARAFURA AND TIMOR SEAS - Widodo S. Pranowo (Widyariset, 2012)
Arafura and Timor Sea is territorial waters which surround three countries of Indonesia, Australia, and Timor Leste. Both seas have very strategic and transboundary conditions, such as for fisheries, sea-climate variability, marine pollutions and others. Therefore, we need studies to understand the characteristics of currents circulation. The most important physical parameters of these features is the dynamics of the upwelling and down welling. Hydrodynamics of 3-D modelling for currents circulation, using tides and wind as initial conditions, is employed to simulating scenarios of the Northwest monsoon, Southeast monsoon, and transition of both monsoons. The results are qualitatively verified. The dynamics of horizontally surface currents follows the monsoon system, and the vertical circulation is significantly exists. Upwelling in coastal waters south of the island of Timor, and between the Islands and the Tanimbar Aru islands appear in all the monsoon due to the influence of the bathymetry. The current circulation is potentially indirect contribution to the fisheries activities in the seas.